PENGUJIAN TINGKAT MOBILITAS MODAL DI INDONESIA DENGAN PENDEKATAN JEFFREY D. SACHS - Aliman Aliman (Faculty of Economics and Business, Universitas Gadjah Mada, 2001)
The objective of this paper is to test capital mobility in Indonesia for the period of 1970-1998 with Jeffrey D. Sachs’s approach. The tools of analysis are cointegration test, Engle-Granger Error Correction Model (EG-ECM), Insukindro-Error Correction Model (I-ECM) and JM test. The empirical results using EG-ECM and I-ECM shows that approach of Sachs’s are useful to identify the degree of capital mobility in Indonesia. The empirical result of EG-ECM and I-ECM for the first approach Sachs failed to identify the degree of capital mobility in Indonesia. However, using second approach of Sachs, the empirical result of EG-ECM and I-ECM show that in the short-run capital mobility in Indonesia is closely perfect—from Indonesia to foreign, but in the long-runs is imperfect. Morever, the empirical result of I-ECM shows shock variable in the short-run influences to current account over the period study. Using JM test, it indicates that IECM is superior than EG-ECM for explaining capital mobility in Indonesia.